The Death of Photograph, the Day After: Alterations of Reality and Experiences Created by Technological Advances - Méndez Moreno, Juan Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The death of photography is argued through its evolutionary step. Nôth, Berger, Dubois, among others, show in their thesis the decadence due to the use of virtual reality and augmented reality devices, innovative gadgets with a fusion of illustrations, frames, audio, interactions, and reactions in an enriched element. The thesis supports three times: moments of its emergence, technological advances, and replacement of traditional media by immersive media. The monographic methodology enables conceptual alignment, concluding that technological advances lead us to a personal representation that is defined by alterations of physical reality, building new experiences.